Does a positive Heaf test reaction in Asian schoolchildren predict later breakdown of tuberculosis?. Issue 10 (October 1992) - Cookson, J B; Cookson, A G
Abstract : BACKGROUND: Some authorities advise giving prophylactic antituberculosis treatment to those with a grade 3 or 4 reaction to Heaf tests performed as part of the schools' BCG programme. This is not done in Leicestershire, which because of its large Asian population would require considerable resources to do so. A calculation of the "breakdown" rate, and thus the potential value of chemoprophylaxis, in these children would therefore be valuable. METHOD: Lists of names of Asian children who had a grade 3 or 4 Heaf test reaction in 1982 and 1983 were compared with lists of notifications for the five years 1983 to 1987. Those who were on both lists were considered to have tuberculosis that had "broken down." RESULTS: Of the 760 children with positive Heaf test reactions, only four were on the subsequent notification lists. The chest radiograph obtained because of the Heaf test result showed evidence of active tuberculosis in only three of these. Only one child had infection that "broke down" later. CONCLUSION: The benefit of chemoprophylaxis seems likely to be limited in these Asian children, most of whom had received BCG early in life.